2018
DOI: 10.1007/s10633-018-9653-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of complete CSNB in the inbred research beagle: how common is CSNB in research and companion dogs?

Abstract: The identified dog had clinical findings consistent with complete type CSNB, similar to that described in the Japanese colony. CSNB appears to be a rare disorder in the wider beagle population, although its detection could confound studies that use retinal function as an outcome measure in research dogs, necessitating careful baseline studies to be performed prior to experimentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…When extrapolated to the On-response it also seems likely that OFF bipolar cells make less of a contribution to the photopic a-wave of the dog than they do in primates [ 29 ]. These findings are further supported by a previously characterized canine model of complete CSNB, wherein the light-adapted On–Off ERG in affected dogs demonstrated a substantially more positive Off-response compared to control dogs (thus indicating a relatively greater role of the ON pathway in the normal canine retina) [ 46 ].…”
Section: Discussionsupporting
confidence: 69%
“…When extrapolated to the On-response it also seems likely that OFF bipolar cells make less of a contribution to the photopic a-wave of the dog than they do in primates [ 29 ]. These findings are further supported by a previously characterized canine model of complete CSNB, wherein the light-adapted On–Off ERG in affected dogs demonstrated a substantially more positive Off-response compared to control dogs (thus indicating a relatively greater role of the ON pathway in the normal canine retina) [ 46 ].…”
Section: Discussionsupporting
confidence: 69%
“…23 Dysfunction of the inner retina in congenital stationary night blindness and acquired conditions like central retinal artery occlusion could also present with an electronegative ERG. 24 Extra caution is advised when analysing the ERG data in the diagnosis and evaluation of interventions in patients with XLRS. 25 In greater detail, intraretinal cysts were found in the NFL from the OCT scanning of both eyes of the current case.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in LRIT3 in humans causes a form of CSNB [139]. The ERG of the affected dogs shows a lack of ON-bipolar cell function with preservation of cone OFF-bipolar contributions [140][141][142]. There is currently debate about the positioning of the LRIT3 protein which had been described as being in the synaptic tips of the bipolar cells; however, a recent publication showed that it was presynaptic, being present in photoreceptors, but bridged the synapse to influence the positioning of post-synaptic glutamate signaling proteins [143].…”
Section: Lrit3mentioning
confidence: 99%